The Effect of Attitudes, Subjective Norms and Perceived Behavioral Control on Consumer Desire and Interest in Purchasing Bicycle Equipment and Supplies through the Marketplace - Pratama, Pratama; Dirgantara, I Made Bayu (Fakultas Ekonomi Universitas Samudra, 2024)
The study aims to examine the effect of attitudes, subjective norms and perceived behavioral control on consumers' desires and behavioral intentions to purchase bicycle equipment and supplies through the marketplace. Sampling used a purposive sampling method, with a total sample of 100 respondents, namely people in Indonesia who in the last one year have been active marketplace users and have purchased bicycle equipment and supplies online. Data was collected using a questionnaire. The data analysis technique uses SEM via AMOS software. The results prove that attitudes, subjective norms and perceptions of behavioral control have a positive and significant effect on consumers' behavioral desires and interests in purchasing bicycle equipment and supplies online through the marketplace.